1999
DOI: 10.1159/000006625
|View full text |Cite
|
Sign up to set email alerts
|

Apomorphine Alters Prey-Catching Patterns in the Common Toad: Behavioral Experiments and <sup>14</sup>C-2-Deoxyglucose Brain Mapping Studies

Abstract: Previous studies on the dopaminergic modulation of visuomotor functions in amphibians showed that the dopamine agonist apomorphine (APO) alters prey-catching strategies. After systemic administration of APO in common toads Bufo bufo, prey-oriented turning and locomotion was attenuated whereas snapping toward prey was facilitated in a dose dependent manner. With systemic APO administration, toads which had previously been hunting, that is pursuing prey, behaved in a waiting position, that is sitting motionless … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
12
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 92 publications
3
12
0
Order By: Relevance
“…These studies combined provide evidence that DA may mediate both motor and reward aspects of amphibian behavior. The results of this present study are not only consistent with previous studies that provide evidence for DA-mediating motor behaviors in frogs [13,[16][17][18]34], these studies combined indicate an evolutionary conservation of DA function across vertebrate taxa. Mean±SEM of the average Trial Time relative to Day 1 for saline and APO-treated animals.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…These studies combined provide evidence that DA may mediate both motor and reward aspects of amphibian behavior. The results of this present study are not only consistent with previous studies that provide evidence for DA-mediating motor behaviors in frogs [13,[16][17][18]34], these studies combined indicate an evolutionary conservation of DA function across vertebrate taxa. Mean±SEM of the average Trial Time relative to Day 1 for saline and APO-treated animals.…”
Section: Discussionsupporting
confidence: 92%
“…Although the systemic administration of APO in this study made it impossible to identify its location of action, we had hypothesized that APO would preferentially impair locomotion based upon two lines of evidence. First, prior studies demonstrated that APO administered at 20 mg/kg body weight in toads impaired such weight-shifting behaviors as turning and lunging [13,15]. Second, pharmacological studies of D2 receptor agonists, such as APO, in general impair locomotor abilities [29].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There are no studies investigating dopaminergic control of reinforcement in frogs. A few studies do show that pharmacological agents acting on dopamine systems affect locomotion [54, 55, 56, 57, 58, 59]. …”
Section: Discussionmentioning
confidence: 99%